Mechanisms of organic reactions - Maskill, Howard; Oxford University Press (Oxford: Oxford University, 2008)
The specialism of organic reaction mechanisms involves not just knowing the currently accepted mechanisms of the more important classes of organic reactions, but also an appreciation of the methodology involved in the investigation of mechanism, and an ability to understand the evidence upon which currently accepted mechanisms are based. Mechanisms of Organic Reactions shows how well-known mechanisms are grounded in experimental observations, so that the basis for reaction mechanisms can be understood rather than simply learned.
Description and investigation of organic reaction mechanisms -- Nucleophilic substitution at saturated carbon -- Elimination reactions to give alkenes -- Reactions of nucleophiles with carbonyl compounds -- Additions to carbon-carbon multiple bonds -- Glossary of terms.
Includes bibliographical references and index.
Keywords: Physical organic chemistry